Study ABO / Rh Systems with IL-18 & IL-33 in Iraqi Patients with Diabetes Mellitus Type II - Baghdad Science Journal (مجلة بغداد للعلوم)
Type 2 diabetes mellitus (DM) is a group of metabolic disorder disease. The inflammatory markers act as a new risk factor for development of type 2 diabetes with a possible association with ABO/Rh blood groups. Human ABO genes are located on chromosome 9q34.1-q34.2. The aim of this study was to investigate the possible association between inflammatory markers, interleukin (IL) -18 and IL-33 in type 2DM and ABO blood groups. Sixty four patients with newly diagnosed type2 DM and control group consist of twenty healthy Iraqi individual. Laboratory test were include ABO blood groups using standard serological procedures and detection IL-18 and IL-33 in serum by ELISA kits. The Present data showed a significant increase in the serum level of IL-18 between type 2 DM patients and control, while there was no significant difference in the serum level of IL-33. At the same time both study blood groups O patients & control showed lowest level of serum IL-18, while blood group A with allele A showed less concentration of IL-33 in patients & control. Blood group O showed the highest percentage in patients & control, also Rh positive showed higher percentage. In conclusion, positive relation between IL-18 concentration and risk of type 2 DM, thus may be a predictor for newly diagnostic diabetic patient, while Serum levels of IL-33 might be a predictor marker of disease progression. No associations were found between ABO & Rh groups with type 2 DM.